[n]Cyclo‐3, 6‐phenanthrenylenes: Synthesis, Structure, and Fluorescence. Issue 16 (19th July 2017) - Tian, Yi; Ikemoto, Koki; Sato, Sota; Isobe, Hiroyuki
Abstract: Five congeners of [ n ]cyclo‐3, 6‐phenanthrenylene with 3, 4, 5, 7, and 8 panels were obtained from one‐pot macrocyclization of dibromophenanthrene, and their crystal structures with diverse molecular shapes were revealed by X‐ray crystallography. The compounds, except the four‐panel congener, were highly fluorescent in solution, with quantum yields up to 85 %. The least fluorescent four‐panel congener showed the smallest change in its absorption spectrum from that of monomeric phenanthrene, which provided an interesting structure–activity relationship for fluorescent macrocycles to guide future studies. Abstract : Highly cyclic : Five congeners of [ n ]cyclo‐3, 6‐phenanthrenylene with 3, 4, 5, 7, and 8 panels were obtained from a one‐pot macrocyclization of dibromophenanthrene, and their crystal structures with diverse molecular shapes were revealed by X‐ray crystallography. The compounds, except the four‐panel congener, were highly fluorescent in solution with quantum yields up to 85 %.